The Retirada: design and evaluation of a teaching proposal for 1st year of Baccaulareate - Banderas Navarro, Néstor; San Miguel Chover, Lara; Pérez Reyes, Adrián; Morales Pérez, Juan Vicente (Clio. History and History Teaching, 2024)
The main objective of this study is to present and evaluate a teaching experience carried out in the 1st year of Baccalaureate on the topic of The Retreat, the Spanish exile in 1939 after the Civil War. To do so, the design of this experience is presented in the context of a Valencian secondary school, carried out in the school years 2022-2023 and 2023-2024, as well as the results of a survey carried out on the students participating in this field trip. This survey confirms the suitability of the activity from a methodological point of view (Erasmus mobility and teaching itinerary), as well as the learning aroused around exile and democratic memory.
Keywords: Exile; Spanish civil war; France; The Retirada; Place of memory